SCIDOT-08. CHILDREN'S BRAIN TUMOUR DRUG DELIVERY CONSORTIUM (CBTDDC). (11th November 2019) - Rahman, Ruman; Campbell, Emma; Brem, Henry; Pearl, Monica; Green, Jordan; Janowski, Miroslaw; Walczak, Piotr; Tyler, Betty; Warren, Katherine; Singleton, Will; Mullen, Alexander; Boyd, Marie; et al.
Abstract: INTRODUCTION: The brain tumour community has seen significant progress in the discovery of new therapeutic targets and anticancer drugs. Unfortunately, advances in how to deliver drugs to the brain lag behind. The blood-brain barrier restricts the entry of many small-molecule drugs and nearly all large molecule drugs that have been developed to treat brain disorders. METHODS: Following an international CNS drug delivery workshop in 2016, we were awarded funding from Children with Cancer UK to launch the Children's Brain Tumour Drug Delivery Consortium (CBTDDC; www.cbtddc.org; @cbtddc). RESULTS: The CBTDDC launched in 2017 (in Europe and the US) to raise awareness of the challenge of drug delivery in childhood brain tumours, and to initiate and strengthen research collaborations to accelerate the development of drug delivery systems. We ran a Workshop on Drug Delivery to the Brain, attracting 52 delegates from the UK, Belgium, Spain and Portugal. We liaised with UK-based funders over the drug delivery agenda, and with UK policy makers. In the US, we jointly organised the SIGN2019 meeting and we are currently liaising with the leads of Project 'All In' DIPG about how we can lend our support to this project. As of June 2019, 150 individuals have registered with the consortium, representing researchers, clinicians, charities, patient groups and industry. These stakeholders represent 70 research institutions, covering 15 countries (France, UK, Italy, Sweden, The Netherlands, USA, Greece, Germany, Belgium, Cuba, Denmark, Spain, Portugal, Israel and Egypt). We host a freely accessible online collaborative research database, containing the details of over 70 researchers. CONCLUSION: We believe that collaboration between clinicians and multi-disciplinary researchers is vital to solving the brain tumour drug delivery challenge. We hope to raise awareness of the CBTDDC, and to extend our invitation for collaborators to join the consortium, through SCIDOT's unrivalled drug delivery platform.